Pengaruh Bahasa Tionghoa Terhadap Bahasa Sehari-hari - Mikhail Perdana; Rudiansyah Rudiansyah (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2021)
The existence of citizens of Chinese descent has been recognized by the Indonesian population, especially residents of Jakarta. Since hundreds of years ago, the ethnic Chinese population has lived in Jakarta, socializing, and socializing closely with the natives. It also affects the history and culture in Jakarta, for example, the style of buildings, food, speech, and clothing. The most noticeable is the use of words that we often use every day. For example, the use of the words